FORMULASI, SIFAT FISIK DAN UJI AKTIVITAS ANTIOKSIDAN MASKER GEL PEEL OFF TEPUNG BERAS HITAM (Oriza sativa L. var Indica) - Mely Nastiti; Desy Nawangsari; Dina Febrina (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Black rice (Oriza sativa L. var Indica) is a local variety that contains anthocyanin pigments. Anthocyanins are antioxidants that have a positive effect on health. Peel off face mask is a face mask that has the advantage that it is easy to remove like an elastic membrane. This study aims to determine the physical evaluation of the peel off gel mask preparation, antioxidant activity and stability of the peel off gel mask. This research method was carried out experimentally, the data were analyzed using the One Way ANOVA method with sig > 0.05. The conclusion of this study was that the black rice flour peel off mask preparation had a significant significant difference to the f1 dispersion test, but there was no significant difference between f2 and 3. There was no significant difference in the antioxidant test. Based on data analysis using one way ANOVA after the cycling test, the formulation was good for 6 cycles, namely formulations 2 and 3. Keywords: Antioxidant, Black rice, dan Peel off mask.